DAMPAK SENGKETA WILAYAH KABUPATEN HALMAHERA BARAT DAN HALMAHERA UTARA TERHADAP PENGELOLAAN PEMERINTAHAN DI DESA BOBANEIGO - Dafrin Muksin; Sahrail Robo (AL IMARAH : JURNAL PEMERINTAHAN DAN POLITIK ISLAM, 2021)
Abstract: This study describes the impact of the dispute over the new autonomous region between West Halmahera and North Halmahera Regencies. Where there is the dualism of government at the village level, namely the villages of Bobaneigo, Pasir Putih, Akelamo, Tetewang, Akesahu, and Dum-Dum which are geographically in the same area. This research is focused on Bobaneigo village as a research location. The method used is qualitative using primary data obtained through interviews and other supporting data. The data that has been collected is sorted out, then coded using Nvivo 12 plus then analyzed and described. The results of this study include: First, the conflict over the expansion of the new autonomous region has resulted in the dualism of village governance, but in a separate service administration. Second, the legitimacy in implementing the governance of Bobaneigo Village, West Halmahera Regency, which is based on history, aspirations, and Perda No. 6 of 2005 concerning the formation of East Jailolo District. Bobaneigo Village Administration, North Halmahera Regency based on Law No. 1 of 2003, PP No. 42 of 1999, and Perda No 2 of 2006 concerning the establishment of Kao Teluk District. Third, government dualism has an impact that greatly affects the level of social welfare, including political, economic, and socio-cultural impacts. Fourth, the factors behind the dualism of government, namely the regulation of Government Regulation No. 42 of 1999 which is not socialized, issues of identity, and the struggle for natural resources currently managed by PT. NHM.Keywords: New Autonomous Region; Territorial Dispute; Village Governance